Development of scalable and versatile nanomaterial libraries for nanosafety studies: polyvinylpyrrolidone (PVP) capped metal oxide nanoparticles - Richard Palmer (RSC Advances, 2017)
The potential long-term environmental impact of manufactured nanomaterials (NMs) remains poorly understood, and the need to better predict NM fate and transformations and chronic effects is particularly urgent. Compared to their bulk counterparts, manufactured NMs can have distinct physical and chemical characteristics, which influence their behaviour, stability and toxicity. It is therefore essential to develop standard and reference NM libraries for environmental nanoscience and nano(eco)toxicology, and to facilitate a move towards computational prediction of NM fate, through quantitative structure–activity relationships for example. The aim of this work was to develop and fully characterise one such library, which included comparable NMs with a range of core chemistries, but the same capping agent and size range, for use in future studies to test the hypothesis that the core chemistry is a primary factor in controlling toxicity. The library contained the following NMs: 10k, 40k and 360k PVP capped ceria, zinc oxide and copper oxide (9 NMs in total). The work presented here upholds the underpinning hypothesis that the mechanism of NM formation is the same in all cases, suggesting that the protocol is very robust and has the potential to generate a wide range of comparable metal oxide NMs and potentially expand the library further with doped metal oxide and metal NMs. Characterisation by means of DLS (both size and zeta measurements), UV/Vis, XPS, FT-IR, TEM, STEM, EDX and EELS confirms that the tested synthesis protocol can easily and successfully be used to create stable PVP capped metal oxide NMs of reproducible sizes.